Production crews: a study of welfare in the Malaysian film and drama industry / Noor ‘Aina Baharudin - Baharudin, Noor ‘Aina (2017)
Freelance production crews in the Malaysian film and drama industry are not being acknowledged in the Malaysian workforce. Their rights as labours towards provision of welfare (income protection and medical and health insurance) and pay rate are indefinite. Information gathered through observation, also interviews with relevant parties in the film and drama industry, namely, production crews, Producers and Professional Film Workers’ Association of Malaysia (PROFIMA) revealed that due to the absence of an Act, income protection is practically null for crews in the industry. Medical and health insurance only provide them with outpatient coverage, while most of the Producers do not provide crews with one, and PROFIMA’s group insurance was not clearly communicated to its members in the industry. The nonexistence of a well-structured pay rate for crews causing them to be exploited by employers and are paid with low rates. Other than that, the attitude of the people in the industry, nonexistence of a legislative body, as well as non-functioning associations are also perceived to be the main contributing factors towards the non-provision of welfare and low pay rate for crews in the industry. Initiatives were done at the lower level by crews, Producers and association to close the gaps, yet the issues still were not solved on the bigger scale. As a workforce, crews’ rights towards provision of welfare including income protection and medical and health insurance, as well as fair pay rate is important not only for their well-being, but also to create a healthy and positive working environment in the Malaysian film and drama industry